Regulation of long-range BMP gradients and embryonic polarity by propagation of local calcium-firing activity - Hyung Chul Lee; Nidia M. M. Oliveira; Cato Hastings; Peter Baillie-Benson; Adam A. Moverley; Hui-Chun Lu; Yi Zheng; Elise L. Wilby; Timothy T. Weil; Karen M. Page; Jianping Fu; Naomi Moris; et al. (Nature Communications, 2024)
Abstract Many amniote vertebrate species including humans can form identical twins from a single embryo, but this only occurs rarely. It has been suggested that the primitive-streak-forming embryonic region emits signals that inhibit streak formation elsewhere but the signals involved, how they are transmitted and how they act has not been elucidated. Here we show that short tracks of calcium firing activity propagate through extraembryonic tissue via gap junctions and prevent ectopic primitive streak formation in chick embryos. Cross-regulation of calcium activity and an inhibitor of primitive streak formation (Bone Morphogenetic Protein, BMP) via NF-κB and NFAT establishes a long-range BMP gradient spanning the embryo. This mechanism explains how embryos of widely different sizes can maintain positional information that determines embryo polarity. We provide evidence for similar mechanisms in two different human embryo models and in Drosophila, suggesting an ancient evolutionary origin.